Dim blue light at night worsens high-fat diet-induced kidney damage via increasing corticosterone levels and modulating the expression of circadian clock genes - Wenji Ren; Zixu Wang; Yulan Dong; Jing Cao; Ting Gao; Qingyun Guo; Yaoxing Chen (Ecotoxicology and Environmental Safety)
Obesity is a contributing factor that increases the likelihood of developing chronic kidney disease. In recent years, studies have found that light pollution worldwide promoted obesity, which was known to be a consequence of circadian rhythm disruption. Nevertheless, the impact of light pollution on kidney disease associated with obesity remains mostly unknown, and potential processes have been minimally investigated. Herein, we fed mice a high-fat diet and gave them dim white (dWL), blue (dBL), green (dGL), and red (dRL) light for 12 weeks. Our results showed that both dWL and dBL tended to be more susceptible to damage to kidney dysfunction caused by a high-fat diet compared to LD, with more pronounced changes in dBL. The analysis of kidney found that dBL activated the TGF-β1/Smad signaling pathway to promote epithelial-mesenchymal transition (EMT) in the kidney. Additionally, dBL activated the NF-κB signaling pathway and resulted in elevated protein levels of TLR4, p-IκB, p-P65, and TNF-α. Furthermore, dBL increased BAX protein levels and decreased BCL2 protein levels. At the same time, dBL affected the Keap1/Nrf2/HO-1 signaling pathway, elevating KEAP1 and decreasing NRF2 and HO-1 protein levels. We were surprised to find that dBL altered the expression of the circadian clock genes, resulting in a decrease in the positively regulated genes Bmal1, Clock, and an increase in the negatively regulated genes Per1, Per2, Per3. Mechanistically, dBL increased plasma CORT levels as well as decreased renal GR α expression, and in vitro experiments showed that the circadian clock genes were altered by the addition of CORT and returned to normal levels after the addition of the GR inhibitor RU486. Consequently, dBL can exacerbate renal injury by elevating plasma CORT levels and altering rhythmic changes by acting on the biological clock via GR.